TPX2 and AURKA promote 20q amplicon-driven colorectal adenoma to carcinoma progression. Issue 11 (29th December 2011) - Sillars-Hardebol, Anke H; Carvalho, Beatriz; Tijssen, Marianne; Beliën, Jeroen A M; de Wit, Meike; Delis-van Diemen, Pien M; Pontén, Fredrik; van de Wiel, Mark A; Fijneman, Remond J A; Meijer, Gerrit A
Abstract : Background and objective: Progression of a colorectal adenoma to invasive cancer occurs in a minority of adenomas and is the most crucial step in colorectal cancer pathogenesis. In the majority of cases, this is associated with gain of a substantial part of chromosome 20q, indicating that multiple genes on the 20q amplicon may drive carcinogenesis. The aim of this study was to identify genes located on the 20q amplicon that promote progression of colorectal adenoma to carcinoma. Design: Functional assays were performed for 32 candidate driver genes for which a positive correlation between 20q DNA copy number and mRNA expression had been demonstrated. Effects of gene knockdown on cell viability, anchorage-independent growth, and invasion were analysed in colorectal cancer cell lines with 20q gain. Colorectal tumour protein expression was examined by immunohistochemical staining of tissue microarrays. Results: TPX2, AURKA, CSE1L, DIDO1, HM13, TCFL5, SLC17A9, RBM39 and PRPF6 affected cell viability and/or anchorage-independent growth. Chromosome 20q DNA copy number status correlated significantly with TPX2 and AURKA protein levels in a series of colorectal adenomas and carcinomas. Moreover, downmodulation of TPX2 and AURKA was shown to inhibit invasion. Conclusion: These data identify TPX2 (20q11) and AURKA (20q13.2) as two genes located on distinct regions of chromosome 20q that promote 20q amplicon-driven progression of colorectal adenoma to carcinoma. Therefore the selection advantage imposed by 20q gain in tumour progression is achieved by gain-of-function of multiple cancer-related genes—knowledge that can be translated into novel tests for early diagnosis of progressive adenomas.